2020
DOI: 10.1097/md.0000000000022736
|View full text |Cite
|
Sign up to set email alerts
|

Association of digestive symptoms with severity and mortality of COVID-19

Abstract: Background: Gastrointestinal manifestations are common in patients with COVID-19, but the association between specific digestive symptoms and COVID-19 prognosis remains unclear. This study aims to assess whether digestive symptoms are associated with COVID-19 severity and mortality. Methods: We will search PubMed, Embase, Web of Science, and the Cochrane Central Register of Controlled Trials up to September, 2020, to identify studies that compared the prevalence of at l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 29 publications
1
7
1
Order By: Relevance
“…However, any possible true difference in mortality may be worth further investigation among better defined patients with COVID-19 subgroups with GI symptoms/ elevated liver enzymes because one study showed that prevalence of severe disease was more common in patients who had GI symptoms than those who did not. 156 Our meta-analysis did not find a statistically significant association between patients with GI symptoms/elevated liver enzymes and ICU admission. However, to investigate such an association, it is important to consider other causes of elevated liver enzymes in patients admitted to ICU such as sepsis, hypoperfusion, hepatotoxic drugs, and parenteral nutrition.…”
Section: Discussioncontrasting
confidence: 59%
“…However, any possible true difference in mortality may be worth further investigation among better defined patients with COVID-19 subgroups with GI symptoms/ elevated liver enzymes because one study showed that prevalence of severe disease was more common in patients who had GI symptoms than those who did not. 156 Our meta-analysis did not find a statistically significant association between patients with GI symptoms/elevated liver enzymes and ICU admission. However, to investigate such an association, it is important to consider other causes of elevated liver enzymes in patients admitted to ICU such as sepsis, hypoperfusion, hepatotoxic drugs, and parenteral nutrition.…”
Section: Discussioncontrasting
confidence: 59%
“…COVID-19 patients who present with GI manifestations, have been found to be more likely to excrete viral RNA in stool [ [69] , [70] , [71] , [72] ], and sometimes have prolonged time to viral clearance [ 73 ], even long after respiratory viral RNA is cleared [ 74 , 75 ]. Since the initial cases reported in Wuhan China, which described low rates of GI symptoms in COVID-19 patients [ 1 , 76 ], the presence of marked digestive symptoms has been described at much higher rates (10% to over 50%) in other cohorts, some out of Wuhan itself [ 6 , 77 , 78 ]. One study investigating the clinical characteristics of COVID-19 in 204 patients, reported vomiting, diarrhea and abdominal pain in 50.5% of cases [ 68 ].…”
Section: Covid-19 the Gut And The Lung-gut Axismentioning
confidence: 99%
“…The patients who presented with atypical symptoms, as gastro-intestinal (GI) symptoms and reduced consciousness, had the highest mortality rate (100%). GI symptoms had an odds ratio of 1.833 (95% CI=0.590-5.697).While, in a published study [25], the odds ratios for nausea and vomiting were (0.63 [0.38-1.04] and 0.92 [0.59-1.44] respectively). Patients who were presented with typical symptoms had (25.6%) mortality rate.…”
Section: Discussionmentioning
confidence: 91%